Combination of endovascular and open repair for the management of subclavian artery injury - Emmanouil Barmparessos; Vasileios Katsikas; Miltiadis Gravanis; Alexios Kalamaras; George Kopadis (Trauma Case Reports, 2022)
Axillosubclavian artery injury is relatively uncommon; however, it is related to a high rate of morbidity and mortality. Although open repair as well as endovascular techniques have been proposed for the treatment of axillosubclavian artery injury, the ideal approach is still under investigation. We present a case of a 20-year-old patient who suffered from complete subclavian artery transection, following blunt thoracic trauma. Using percutaneous access, a balloon catheter was inflated under fluoroscopy, in the origin of his affected subclavian artery ceasing the haemorrhage, thus immediately afterwards he was submitted to arterial bypass. The combination of endovascular and open repair ensured his life and limb salvage while the complications of an otherwise extensive dissection were obviated.